Comparison between Giving Warm Water Compressions and Sour Tamarind Drink on Primary Dysmenorrhea - Aan Andriani; Bunga Tiara Carolin; Nurul Husnul Lail (KHD-Production, 2022)
Primary dysmenorrhea is very painful menstruation, with no visible pelvic pathology and can occur at the time of menarche or immediately after. One way to overcome dysmenorrhea is by using non-pharmacological strategies, namely warm water compresses and drinking sour turmeric. This study aims to determine the comparison between offering warm compresses and sour turmeric drink to primary dysmenorrhea This study uses a Quasy Experiment with a one-group pretest-posttest design approach. The sample in this study revealed 40 female students consisting of 20 groups before and after being given warm water compresses and 20 groups before and after being given turmeric acid. The sampling technique used purposive sampling. In this study using an observation sheet (Faces Pain Rating Scale). Data analysis used Skewness and Kurtosis test and paired sample T-test and Independent T-test. The results of the study using the Independent T-test showed that there was no difference before and before giving warm air compresses with a Sig value. 0.911 > 0.05, and drinking tamarind turmeric was 0.797 > 0.05, for primary dysmenorrhea in students of SMK N 3 Taliabu Utara with a score of There is no difference in the effect between before and before giving warm and acid compresses to primary dysmenorrhea in female students of SMK N 3 Taliabu Utara. It is hoped that it can be applied to students who experience primary dysmenorrhea